Interview: 'The elephant in the room': talking (physics of) blackness with Michelle M. Wright. - Phiri, Aretha; Wright, Michelle M. (Cultural Studies, 2023)
The article presents an interview with Michelle M. Wright talking about global inequalities and injustices. Topics include discussing the work in the context of turbulent global race politics and increasingly ethno nationalist populism; and displacement in academia of an African American monopoly on Black discourse(s) and blackness scholarship.